Diagnosis, treatment, surgical practices and review of the literature in rare coagulation factor deficiencies - Hüseyin Avni Solgun (Italian Journal of Pediatrics)
Abstract Background Rare bleeding disorders (RBDs) include fibrinogen (Factor I), prothrombin (Factor II), Factor V(FV), combined Factor V and Factor VIII, Factor VII, Factor X, Factor XI, Factor XII, and Factor XIII deficiencies. This group accounts for 3–5% of all factor deficiencies. Different symptoms may occur, ranging from mild or moderate bleeding to serious and life-threatening bleeding, which may not be related to the factor level. This study aimed to evaluate the diagnosis, genetics, treatment, prophylaxis features and surgical experiences of patients those are followed up in our clinic and the review of the literature of rare factor deficiency. Methods Demographic data, number of follow-up visits throughout the study period, clinical symptoms, number and locations of bleeding symptoms of 19 patients diagnosed with RBD (fibrinogen, prothrombin, FV, FVII, FX, FXI or FXIII) who were followed up in our pediatric hematology clinic between year 2023–2024 and complications, inhibitor levels, previous operations, treatment and prophylaxis approaches are recorded in the patient chart and all data had been evaluated retrospectively. In our article, all patients included in this study are mentioned according to the consecutive numbering system as Patient 1(P1) to P19 in Table 2. A comprehensive literature search was performed in PubMed and after primary elections 4 studies are selected from total 23 studies those are most relevant to RBDs in pediatric age as there is only plenty of articles about RBDs. Most of the other studies are reviews without clinical patient trails just including recommadations for diagnosis and laboratuary screenings. In contrast, our study includes a clinical trail on diagnosis, treatment and prophylaxis information of 19 patients with RBDs. Results The average age of total 19 patients was 11.2 years (range 2,5–17 years). 14 patients were boys (74%) and 5 patients were girls (26%). 10 of the patients (52%) had FVII deficiency (mean FVII: 8,3%, range 2,5–17%), 4 of patients (21%) had FX deficiency (mean FX:16,2%, range 15–17%) and 4 of patients (21%) had FV deficiency (mean FV:14%, range 10–17%) and 1 had FXIII deficiency (1%) respectively. The normal range laboratory reference values for rare blood factor levels in our institute (factor V, VII and X deficencies) is 70–120%. In our study group, 63% (12/19) of our patients were diagnosed over one year of age. Considering all of our cases, skin and soft tissue bleedings are listed as 52% (10/19), intraoral bleedings as 42% (8/19), nose bleedings as 63% (12/19), joint bleedings as 42%(8/19) and santral nerveous system(CNS) bleedings as 15%(3/19). Among the serious bleedings of our cases, joint bleeding 42% (8/19) takes the first place with followed by CNS bleeding 15% (3/19) and gastro-intestinal system(GIS) bleeding (15%) (3/19) respectively. Among totally 19 patients, FX deficiency-P17 had a null mutation of FX gene and FV deficiency-P3 had a missense mutation of FV gene has been detected those both were severe deficencies. The medical genetics of the sibling patients with combined FVII deficency and hypofibrinogenemia have been evaluated, but the genetic results have not been completed yet. Conclusions We believe that data-based service is required in every clinic and healthcare system for early diagnosis and follow-up of RBDs. Additionially family screenings and more effective genetic counseling may heal the overall survival and prevent further severe complications. Moreover; the missing factor, severity of deficiency, personal and family history of bleeding or thrombosis, availability of treatment options, plasma half-life of infused exogenous clotting factors and infusion frequency, advantages and disadvantages should all be considered before a prophylaxis program or treatment of RBDs.